Anti-hyperglycemic Potential of methanolic extract fraction of Trichuriella monsoniae (L.f.) Bennet - Vanapatla Swaroopa Rani,; Praneetha P,; Krishna Mohan G,; Ravi Kumar B, (International Journal of Phytomedicine, 2014)
The anti-hyperglycemic activity of methanolic extract fraction of Trichuriella monsoniae (TM) was evaluated in Streptozotocin induced diabetic rats. Methanolic extract was fractionated and subjected to antidiabetic studies in streptozotocin induced diabetic rats to identify the most potent bioactive fraction. Oral administration of fractions of METM at 20 & 40 mg/kg b.w. significantly reduced the fasting blood glucose levels in diabetic rats. Among the fractions, n- butyl alcohol fraction (BLTM) at 40 mg/kg b.w. was found to be more effective. Further, in sub-acute study, BLTM significantly reduced the elevated level of glucose, cholesterol, triglycerides, insulin, SGPT, ALP, creatinine in serum and increased the diminished body weight and total protein and insulin level in serum in streptozotocin induced diabetic rats. Increased glycogen content was observed in liver and skeletal muscle of the diabetic rats after 28 days of the treatment. BLTM ameliorated the histological damage of islets of langerhans. BLTM also elicited a significant antioxidant effect, which was evident from its ability to inhibit lipid peroxidation and also by scavenging the DPPH radical. The results of the study clearly indicate that BLTM exerts potent antidiabetic activity.